"TAPEL for postpartum pain reduction " - Asirotul Marifah Marifah; Naning Puji Suryantini (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Tapel is a traditional medicine in the form of solid, pasta or like porridge used by smearing on the mother's abdomen after delivery. Tapel causes touch to the skin that is, a sense of cold, warm and also a refreshing smell. So it is possible that the element can reduce the pain Afterpain due to uterine contractions that are sometimes very disturbing mainly 2-3 days Postpartum. The effectiveness of Tapel use in postpartum mothers was analyzed using descriptively by correlating tapel administration to afterpain. From the result of data analysis using Wilcoxon test got that value of a-Symp. Sig (2 tailed)) of 0,000 due to asymp.sig (2-tailed) <Î± 0.05. The puerperal mother given Tapel gets distraction from the tapel. This is due to the cold sensation and the warm feeling that the patient feels when Tapel is smeared into the front of the stomach as well as the refreshing tapel smell (the smell of traditional medicine) makes a distraction in the mother who experiences Afterpain. Keywords: Tapel, Afterpain, Post Partum